Physical activity and quality of life of patients with inflammatory bowel disease. Issue 27 (9th July 2021) - Kim, Bun; Chae, Jisuk; Kim, Eun Hye; Yang, Hyuk In; Cheon, Jae Hee; Kim, Tae Il; Kim, Won Ho; Jeon, Justin Y.; Park, Soo Jung
Abstract : Abstract: This study examined the association between physical activity (PA) and quality of life (QOL) in Korean patients with inflammatory bowel disease (IBD). We enrolled 158 patients with IBD (81 men and 47 women). PA levels were assessed using the International PA questionnaire. Using self-reported frequency (day) and duration (h) of physical activities, the patients were categorized into 3 groups based on their total metabolic equivalent (MET-h/wk) values: least, moderate, and most active. The QOL of patients with IBD was assessed using the inflammatory bowel disease questionnaire (IBDQ), the Medical Outcomes Study 36-Item Short Form Version 2 (SF36v2), the EuroQOL five dimensions questionnaire (EQ5D), and the EuroQOL visual analog scale (EQ-VAS). Of 158 patients, 62, 73, and 23 patients with Crohn disease, ulcerative colitis, and intestinal Behçet disease, respectively, were included. The mean age was 45.96 ± 17.58 years, and 97 (61.4%) patients were men. Higher PA levels correlated with higher EQ5D and EQ-VAS scores ( P  < .001 and P  = .004 respectively). In addition, depending on the type of PA, the amount of leisure activity was associated with higher IBDQ ( κ  = 0.212, P  = .018), physical function of SF36v2 ( κ  = 0.197, P  = .026), EQ5D ( κ  = 0.255, P  = .002), and EQ-VAS ( κ  = 0.276, P  = .001) scores. The frequency of sweat-inducing exercise showed an inverse correlation with IBDQ ( κ  = –0.228, P  = .011), physical function of SF36v2 ( κ  = –0.245, P  = .006), EQ5D ( κ  = –0.225, P  = .007), and EQ-VAS ( κ  = –0.246, P  = .004) scores. Increased PA levels were associated with improved QOL in patients with IBD. More leisure activity and non-sweat-inducing exercise were associated with improved QOL in patients with IBD.